Letter to editor - Reichmann JP (Dove Medical Press, 2013)
James P ReichmannSales & Marketing, American HomePatient, Brentwood, TN, USA, I would like to congratulate the authors of the article entitled, "Optimal management of nausea and vomiting of pregnancy" for the comprehensive review of treatments for a frequent complication of pregnancy.1 Although this letter arrives well after publication I think it is important for researchers in the future to have clarification on one seemingly minor but important point. In order to avoid confusion it must be pointed out that in the metoclopramide section the statement "subcutaneous metoclopramide is effective in many women with NVP and HG" is supported by one observational trial on continuous subcutaneous metoclopramide.2 This distinction is very important because that study reported patients were receiving the drug for 26.7 days on average at a cost of $4432 per patient. Unfavorable cost comparisons have been previously published.3 The recommendation that more studied and less expensive alternatives are explored prior to subjecting the patient to this extreme measure seems prudent.4 Perhaps the use of the reference to continuous subcutaneous metoclopramide may have been accidental but the suggestion that "these findings are reassuring, especially for women who experience excessive sleepiness…" implies that women on Diclectin® who report being tired are advanced to continuous subcutaneous metoclopramide seems like a waste of health care resources and a little reckless.1View original paper by Ebrahimi and colleagues.